Peran Guru Pendidikan Agama Islam Dalam Menanamkan Sikap Toleransi Siswa di SDN Pekuncen Kota Pasuruan - Muhammad Sulaiman (IAI Darussalam, 2024)
Religious tolerance education in elementary schools has become crucial in the current era of globalization and multiculturalism. SDN Pekuncen Kota Pasuruan plays a significant role in fostering students' tolerance towards religious diversity, with Islamic Religious Education (PAI) teachers as the key actors. This study aims to describe the role of PAI teachers as motivators and guides in cultivating religious tolerance at SDN Pekuncen Kota Pasuruan. This article employs a qualitative approach with a case study research design, collecting data through observations, interviews, and documentation from PAI teachers, students, and classroom teachers, and analyzed descriptively. The findings indicate that PAI teachers are effective in motivating students to accept religious differences and guiding them in developing attitudes of mutual respect, honoring others, and doing good.